Interrelationships Between Bones, Muscles, and Performance: Biting in the Lizard Tupinambis merianae - Fabre, Anne-Claire; Andrade, Denis V. [UNESP]; Huyghe, Katleen; Cornette, Raphael; Herrel, Anthony (Springer, 2014)
The origins of and potential constraints on the evolution of phenotypic diversity remain one of the central questions in evolutionary biology. The vertebrate skeleton is governed by historical, developmental, architectural, and functional constraints that all play a role in establishing its final form. Whereas the factors underlying shape variation in single bones are fairly well understood, this is less so the case for complex assemblages of bones as observed in the cranium or mandible. It is often suggested that the final phenotype must reflect the mechanical constraints imposed by the loading of the skeleton as bones remodel to withstand loading. Yet, in the cranium, in contrast to the mandible, the final phenotype is likely constrained by demands other than loading including the protection of sensory systems and the brain. Architectural design constraints may further limit the final form of complex units like the vertebrate cranium. Here we use geometric morphometric approaches to quantify the shape of the cranium and mandible in a lizard and test whether the observed shape co-varies with both the muscles attaching to these structures as well as functional traits such as bite force. Our results show that co-variation between the cranium and mandible is significant and likely driven by the muscles that link the two systems. Moreover, our results show that the patterns of co-variation are stronger between the mandible and ventral side of the cranium. Muscular cross sectional areas, bite force, and the ventral side of the cranium, also co-vary more than the dorsal side of the cranium does with muscle properties and function. Finally, our results show sex-specific patterns of co-variation with males showing a stronger degree of integration between the cranium, mandible, muscles and bite force suggesting that constraints on bite force drive the evolution of cranial shape to a greater extent in males compared to females.
Keywords: Morphometrics; Covariation; Function; Cranium; Mandible